THE EFFECT OF RHEUMATIC GYMNASTIC AND SHALAWAT NARIYAH ON THE PAIN LEVEL OF GOUT ARTHRITIS PATIENTS - Damayanti, Betty Shinta; Faridah, Virgianti Nur; Lestari, Trijati Puspita (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Uric acid levels in the blood exceeding normal limits can cause a buildup in the joints and organs. This buildup causes the joints to feel sore, painful and inflamed. This study aimed to determine the effect of Rheumatic Gymnastics and Shalawat Nariyah on the pain level of patients with gout arthritis. This study used a pre-experimental one-group pre-posttest design. A total of 34 respondents were obtained by total sampling. The instrument was the Numeric Rating Scale. The results showed that before being given the intervention, 23 people (67.6%) experienced moderate pain, while after being given the intervention, 19 people (55.9%) experienced mild pain. The hypothesis was tested using the Wilcoxon test with the results (P = 0.000 ≤ α 0.05), meaning that Rheumatic Gymnastics and Shalawat Nariyah had an effect on pain levels in patients with gout arthritis. Rheumatic Gymnastics and Shalawat Nariyah can stimulate an increase in the release of endorphin hormones and cause a relaxing effect on reducing pain in patients with gout arthritis.